2003
DOI: 10.1063/1.1607239
|View full text |Cite
|
Sign up to set email alerts
|

RHIC Spin Flipper Commissioning

Abstract: Here, &I is the unit vectors pointing radially outward and An ac dipole with horizontally oriented oscillating magnetic field (spin flipper) was installed in FU-IIC to reverse the spin direction in the presence of two full Siberian snakes, thereby reducing the systematic errors for the spin physics experiments in RHIC. With two full snakes, the spin vector completes one full precession around the vertical direction in two revolutions, and the spin depolarization resonances due to the machine imperfections and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…It is planned to develop an AC dipole that will efficiently reverse the polarization of the stored beam [14]. This tool, used in conjunction with changes in which beam bunches overlap (recogging), will be fully developed in subsequent RHIC runs.…”
Section: Spin Asymmetry Measurements In a Collidermentioning
confidence: 99%
“…It is planned to develop an AC dipole that will efficiently reverse the polarization of the stored beam [14]. This tool, used in conjunction with changes in which beam bunches overlap (recogging), will be fully developed in subsequent RHIC runs.…”
Section: Spin Asymmetry Measurements In a Collidermentioning
confidence: 99%
“…It was observed that part of the polarization loss is caused by the strong intrinsic resonances during beam acceleration in RHIC [2,3] despite the presence of Siberian snakes. In addition, despite upgrades of the spin flipper system [4][5][6][7][8] and improvement of the related closed orbit bump, spin polarization was not well preserved during spin flipping experiments until the optics was modified for reducing the spin tune spread. As described in this report the modification consists in minimizing the difference of the dispersion derivatives (dispersion primes) between the two Siberian snakes [9] used for polarization preservation.…”
Section: Introductionmentioning
confidence: 99%
“…At the RHIC polarized proton collider, an effort is underway to implement fast spin reversal of the stored polarized proton beam. A new spin flipper design has been developed [20] which is compatible with the spin tune of ½ in RHIC with its two pairs of full Siberian snakes.…”
Section: Fast Spin Reversal In Rhicmentioning
confidence: 99%